Thermal Analysis of Si/GaAs Bonding Wafers and Mitigation Strategies of the Bonding Stresses - Yuanying Qiu; Xun Qiu; Xianghu Guo; Dian Wang; Lijie Sun (Advances in Materials Science and Engineering)
In order to effectively reduce the thermal stresses of Si/GaAs bonding wafers during their annealing process, first of all, based on E. Suhir’s bimaterial thermal stress theory, the thermal stresses in the wafer bonding interfaces are analyzed and the thermal stress distribution formulas are obtained. Then, the thermal stress distribution curves of Si/GaAs bonding interfaces are investigated by finite element method (FEM) and are compared with the results from E. Suhir’s bimaterial thermal stress theory. Finally, some effective strategies are proposed to reduce the thermal stresses in the bonding interfaces.